2014
DOI: 10.1136/bcr-2014-204690
|View full text |Cite
|
Sign up to set email alerts
|

Aleukaemic leukaemia presenting with pathological fracture

Abstract: A 19-month-old Chinese girl presented with pathological fracture of her right distal tibia. Peripheral blood revealed no abnormal cells, electrolytes were normal and bone biopsy at the fracture site only showed small aggregates of unremarkable lymphocytes. A bone marrow study could not provide a definitive diagnosis of acute leukaemia on morphology and immunohistochemistry. A diagnosis of precursor B-cell acute lymphoblastic leukaemia was unequivocally confirmed by a cytogenetic study which showed a hyperdiplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The clinical union was ultimately achieved as peripheral blast cell count considerably low (±10-14%). A similar outcome has also ever been reported by Chua et al who observed fracture healing along with the bone marrow remission post-chemotherapy in a pediatric aleukemic leukemia case [24].…”
Section: Discussionsupporting
confidence: 86%
“…The clinical union was ultimately achieved as peripheral blast cell count considerably low (±10-14%). A similar outcome has also ever been reported by Chua et al who observed fracture healing along with the bone marrow remission post-chemotherapy in a pediatric aleukemic leukemia case [24].…”
Section: Discussionsupporting
confidence: 86%
“…The rare presenting features of this pre B-ALL patient, lytic bone lesions with normal platelet and leukocyte count has been described previously, particularly in pediatric patients (9)(10)(11) where it is uncommon, but also in a handful of adult cases (6,7). The two adult cases with bone lesions B-ALL and near normal hemograms, were positive for CD19, CD10, and HLA-DR, (and other B cell markers).…”
Section: Discussionsupporting
confidence: 59%
“…Treatment must be tailored to both the fracture and the underlying cause. 4 Here, we report the case of a child who experienced a spontaneous left fibular fracture (with no event/accident of trauma to cause it) and whose scans revealed a lytic lesion, which yielded various differential diagnoses including eosinophilic granuloma, Ewing sarcoma, and leukemia.…”
Section: Introductionmentioning
confidence: 99%